A note concerning the use of classificatory techniques by police for analyzing crime areas - Meyer, John C. (American journal of criminal justice, 1979)
These research notes present one approach to the analysis of crime areas within police jurisdictions. Association Analysis appears to be a useful method to not only classify crime areas but also to discover crime patterns within those areas. This approach is briefly discussed and an example given to illustrate its application. Other methods and areas of application are also mentioned and discussed.